„Pamięć nie wybacza”. O Białej Rice Magdaleny Parys - Natalia Żórawska (Postscriptum Polonistyczne)
Biała Rika (White Rika, 2016) presents the trauma of a third generation. Magdalena Parys, referring to autobiographical motifs, recalls past events – the difficult childhood of the main character, specific family relations, and the tragic experiences of a so‑called grandmother. The author of the article discusses the types of trauma connected with the experience of war, unsuccessful relationships within a family and the period of growing up. She concentrates on female characters, as the women in Biała Rika represent a wide variety of women with different features and values. The aim of the article is to interpret Biała Rika in the context of post‑trauma with past torments and the work of memory always in the background of one’s consciousness.